Using Fuzzy Logic in the Critical Process Controlling - Spalek, Juraj; Molnarova, Monika (Communications - Scientific Letters of the University of Zilina, 1999)
In this paper the advantages of fuzzy logic used for two - channel systems output comparison in safety - related critical applications have been presented. The paper deals with the design of the fuzzy logic - based comparator that compares the data of traction vehicle velocity in target braking process and its optimisation using the ANFIS method. Some failures of the system in Matlab - Simulink environment have been simulated. The result is the analysis of ailures consequences from the point of system safety.